Augmented Reality in Mathematics Education: Evaluation of the Effect of Interactive Books on Student Motivation and Understanding - Atik Prihatini; Laelasari (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research evaluates the effectiveness of Augmented Reality-based mathematics books (MathAR Book) in increasing motivation and understanding of mathematics concepts for high school students by comparing them with conventional books. Two classes were randomly selected using an experimental design: one using the MathAR Book and one using a conventional book. The analysis results show that although MathAR Book makes learning more interactive and exciting, there is no significant difference in motivation and understanding of mathematics compared to conventional methods. Student motivation did not increase significantly, and Cohen's d showed a small effect. In-depth interviews and focus group discussions revealed students' enthusiasm for augmented reality (AR) technology and technical barriers such as slow applications and a lack of detailed guidance. Students familiar with technology feel more comfortable, while those less familiar find it difficult. Suggestions for improvement include improving the user interface and better integration with conventional textbooks. Mathew's Book has the potential to improve mathematics learning and student motivation. However, its success depends on adequate technical and pedagogical support and effective integration with traditional learning methods. Further research is needed to overcome these obstacles and optimize the design of the MathAR Book.